EXTRACTION METHODS OF DIATOMS-A REVIEW (Indian Internet Journal of Forensic Medicine and Toxicology, 2006)
Detection of diatoms in tissues has been applied as an important sign of drowning since the beginning of 20th  century and utility of diatoms for the diagnosis of drownings cases was debated soon after they were first found  in lung exudates. Hard bones (sternum and femur) and soft tissues (lungs and liver etc) of drowned bodies are  usually sent to the Forensic Science Laboratories for the detection of diatom. Dissolution of these samples is not  very difficult but complete extraction of diatoms frustules from these samples needs great care, attention and  expertise. While solving drowning cases, a correlation between the diatoms extracted from these tissue samples   and the samples obtained from putative drowning medium has to be established for the successful determination  of drowning site. Therefore, it needs proper method for extraction of diatoms from tissues and water samples to  avoid even minor contamination. In the present study, literature related with various extraction methods of  diatoms from postmortem and water samples has been reviewed.
Keywords: Drowning; Diatoms; Bone marrow,; Centrifugation